Dynamic influences of nutrients and grazing fish on periphyton during recovery from flood. - Murdock, Justin N.; Dodds, Walter K.; Gido, Keith B.; Whiles, Matt R. (My University, 2011)
Nutrients and grazers both can regulate benthic algal structure and function in streams, but the relative strength of each factor depends on stream biotic and abiotic conditions. The abundance of stream organisms and nutrient availability can change rapidly after a flood. Thus, nutrient and grazer influences on algal development and how these drivers interact may vary temporally during recovery. We measured benthic structural and functional development for 35 d after a simulated flood in large outdoor mesocosms under a gradient of 6 nutrient loadings crossed with 6 densities of grazing fish (Southern redbelly dace, Phoxinus erythrogaster). Nutrients influenced algal development more than dace did and were better correlated with algal function (area-specific primary productivity and nutrient uptake) than with structure (biomass). Dace influenced all structural variables and biomass-specific gross primary productivity, but their influence was relatively weak and was observed only early in recovery. Dace influence weakened and nutrient influence strengthened during recovery. Understanding context-dependent relationships in postdisturbance community dynamics is essential for predicting ecosystem responses to future changes in nutrient inputs and biodiversity, particularly in systems, such as headwater streams, with frequent disturbance.
Keywords: Algae; Benthic; Bottom-up; Disturbance; Stream; Top-down; Mesocosm